A FLEBITE COMO UMA DAS PRINCIPAIS INTERCORRÊNCIAS NA TERAPIA INTRAVENOSA PERIFÉRICA EM ADULTO - Santana, Maria Messias dos Santos (2020)
Objective: To analyze the occurrence of phlebitis as one of the main complications of peripheral intravenous therapy in adults. Methodology: Articles from the SCIELO, LILACS and BDENF databases were used to carry out an integrative literature review. Results: The selection of 14 articles made it possible to identify the main incident factors of phlebitis. Conclusion: phlebitis can be considered one of the main complications of IVT due to factors such as the type of medication, the catheter gauge and the puncture and infusion time, among other less prevalent factors, according to the studies analyzed.